2016
DOI: 10.1080/14658011.2016.1159778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle morphology on viscoelastic and flexural properties of epoxy–alumina polymer nanocomposites

Abstract: Nanocomposites were synthesised by dispersing two different types of alumina nanoparticles in epoxy matrix by ultrasonication. Alumina nanoparticles of two shapes, rod and spherical were selected to investigate the effect of particle morphology on viscoelastic and flexural properties of nanocomposites. Specific surface area of both the selected nanoparticles was kept in the similar range. Good dispersion of nanoparticles was observed through transmission electron microscopy. The addition of nanoparticles in ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The loading of nanoparticles (NPs) into polymeric matrices generally yields a mechanical reinforcement of the polymer nanocomposites (PNCs) relative to the neat polymer host, even at low NP loadings. The growing availability of NPs with controllable affinities and the development of instrumentation to probe small length scales have spurred renewed studies in mechanical reinforcement as well as viscoelasticity of PNCs. A detailed study of the mutual interplay between NPs and host polymer chains, linking structural properties, modified relaxation dynamics of polymer chains and NPs, and dynamic mechanical and rheological properties of PNCs, is imperative for quantitative and predictive engineering of function-specific PNCs. …”
mentioning
confidence: 99%
“…The loading of nanoparticles (NPs) into polymeric matrices generally yields a mechanical reinforcement of the polymer nanocomposites (PNCs) relative to the neat polymer host, even at low NP loadings. The growing availability of NPs with controllable affinities and the development of instrumentation to probe small length scales have spurred renewed studies in mechanical reinforcement as well as viscoelasticity of PNCs. A detailed study of the mutual interplay between NPs and host polymer chains, linking structural properties, modified relaxation dynamics of polymer chains and NPs, and dynamic mechanical and rheological properties of PNCs, is imperative for quantitative and predictive engineering of function-specific PNCs. …”
mentioning
confidence: 99%
“…Due to the formation of agglomerates, the nano‐Al 2 O 3 did not create a chemical bond appropriately with epoxy in the matrix. Hiremath and Shukla 31 observed that at high wt% of nano‐Al 2 O 3 , the viscosity of nanocomposites increases because a non‐uniform dispersion of nano‐Al 2 O 3 takes place in the matrix. At higher wt% of nano‐Al 2 O 3 , the distance among the nanoparticles reduced in 0.1 mm thickness of the adhesive layer.…”
Section: Discussionmentioning
confidence: 99%
“…Spherical‐shaped nano‐Al 2 O 3 (nanospheres) was provided by Nanostructured and Amorphous Materials, Inc. Sigma‐Aldrich Corporation, India provided rod‐shaped nano‐Al 2 O 3 (nanorods). The properties of the adherend, adhesive 31 and nano‐Al 2 O 3 31 are mentioned in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Load transfer between particles and EPDM matrices contribute toward the flexural strength of the composites. 44 Flexural properties found to increase upon irradiation comparing to unirradiated samples. The flexural properties found to be related to the crosslinking of the EPDM composites.…”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…Flexural modulus is a measure of a materials stiffness or resistance to bending action, the sampling configuration is known as the threepoint bend test. 44 The flexural properties are measured by using Dynamic Mechanical Analyzer up on a constant frequency and temperature in rubbery region at 25 C. Figure 5 shows the effect of irradiation doses on the flexural characteristics for four EPDM blends with different wt% of fillers (W, BaSO 4 ). Load transfer between particles and EPDM matrices contribute toward the flexural strength of the composites.…”
Section: Mechanical Propertiesmentioning
confidence: 99%